If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22y + -4 = 4y + -2 Reorder the terms: -4 + 22y = 4y + -2 Reorder the terms: -4 + 22y = -2 + 4y Solving -4 + 22y = -2 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -4 + 22y + -4y = -2 + 4y + -4y Combine like terms: 22y + -4y = 18y -4 + 18y = -2 + 4y + -4y Combine like terms: 4y + -4y = 0 -4 + 18y = -2 + 0 -4 + 18y = -2 Add '4' to each side of the equation. -4 + 4 + 18y = -2 + 4 Combine like terms: -4 + 4 = 0 0 + 18y = -2 + 4 18y = -2 + 4 Combine like terms: -2 + 4 = 2 18y = 2 Divide each side by '18'. y = 0.1111111111 Simplifying y = 0.1111111111
| y+30+y+40=180 | | 25-In(3-x)=0 | | 30+5m=30+7m | | 60/30=x/(6-x) | | 3+4x=3x+4 | | 25p+12=26.46 | | 10.20=11b+b | | 3x+25=27 | | Y+20=2x | | 1x-3=11 | | 3b+48=5 | | 2(x)-12=40 | | 13-3m=-5(2m+3) | | 2((2m+3)-1(1-2m))=2(3(3+2m)-3(3-m)) | | 4x^2+12x-14=0 | | 72b^2=4 | | 90=x*18 | | 4m+2b=28 | | 2a-5whena=7 | | 30+d=30+d | | 1/3h-4(2/3h-3)=2/3-3 | | -x*-x+2x*2x=11.33 | | log(7)x-log(7)(x-1)=1 | | 2.67(18)+x(6)=3 | | 4(x-5)=11(x+2) | | 5m+2n=10 | | -16=x/7 | | (3xy)^2/y^2= | | 4x+(5x+4)=134 | | (3xy)^2/y^2 | | -2/9=7/x | | 1.7(2)=n |